Determining the effect of the amount of polypropylene fiber and plasticizer on the strength and abrasion resistance of concretes for rigid pavement - Kroviakov, Sergii; Finohenov, Oleh; Ihnatenko, Andrii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is concretes and fiber-reinforced concretes for rigid pavements with polypropylene fiber and lignosulphonate type plasticizer. The task addressed is obtaining concrete with increased strength and wear resistance. Three compositions factors were varied in the experiment conducted according to the D-optimal plan: the amount of cement (300–380 kg/m3), plasticizer based on lignosulfonates (0.6–1.0 %), polypropylene fiber with a fiber length 39 mm (0–3 kg/m3). All concrete mixtures had equal mobility S1. A set of experimental and statistical models was calculated. It was found that with an increase in the amount of plasticizer, the W/C ratio of the mixture decreases by 12–15 %, and the introduction of fiber has a negligible effect on W/C. Due to the use of fiber, the compressive strength of concrete at the design age increases by approximately 3.5 MPa, the early compressive strength practically does not change, the flexural strength increases by 0.5–0.6 MPa, and the abrasion resistance decreases by 0.07–0.08 g/cm2 (17–19 %). The most noticeable changes in these properties occur already with the introduction of fibers in the amount of 2–2.5 kg/m3. Increasing the amount of cement improves the strength and wear resistance of concrete, as well as the efficiency of using dispersed reinforcement. When the amount of plasticizer is increased from 0.6 to 0.9 %, the compressive strength of concrete at the age of 3 days increases by approximately 2 MPa; at the design age, its strength increases by approximately 5 MPa, the flexural strength increases to a limited extent while the abrasion of concrete decreases (wear resistance increases). Due to dispersed reinforcement and the use of a rational amount of plasticizer, concretes of rigid pavements with the required strength and increased wear resistance required for a given road category with reduced binder consumption were obtained, which could be used in practice